Green Generation: Inisiasi Gen Z dalam Membangun Revolusi Green Economy bidang Pangan - Fahrillah, Ahmad; Kurniawan, M. Edo; Barory, Chulil; Yudowati , Dewi Mumpuni (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2025)
The global food crisis, climate change, and environmental degradation present real challenges that require innovation and the transformation of the food system toward a Green Economy. Generation Z, characterized as digital natives who are highly adaptive to technology and deeply concerned about environmental issues, has the potential to become a Green Generation leading the green economic revolution in the food sector. This study aims to examine Gen Z’s initiatives in building a Green Economy in the food sector, analyze the strategies implemented, and identify supporting and inhibiting factors. A descriptive qualitative approach was applied through literature review, policy analysis, and case studies on young farmer programs and sustainable food innovations. The findings reveal that Gen Z contributes to the development of precision agriculture, organic farming, and diversification of environmentally friendly food products based on local wisdom. These initiatives strengthen national food security, create green business opportunities, and establish a sustainable food ecosystem. In conclusion, Gen Z’s active role in the food sector is the key to accelerating the Green Economy revolution, with success highly dependent on policy support, technical assistance, and cross-sector partnerships.